The role of the pharmacist in the use of leuprorelide to block puberty - Jesuíno, Simone dos Santos; Quintilio, Maria Salete Vaceli (Revista Coleta Científica, 2022)
Precocious puberty syndrome is characterized by premature bodily sexual maturation, before the time considered physiologically normal. Leuprorelin, also known as leuprolide, is the most commonly used drug for the treatment of precocious puberty disorders, acting directly on the production of hormones. This literature review study is guided by the search to understand the role of the pharmacist as an intermediary in the continuity of the treatment of precocious puberty using leuprorelin. Free databases were consulted, covering a period of 5 years. Leuprorelin is shown to be effective in the regression of the secondary characteristics of Tanner's stage, reducing gonatropin levels and acting in the non-progression of the child's bone age. Pharmaceutical care should be considered as fundamental in the approach of families diagnosed with precocious puberty and the professional's dialogue with the family to reduce anxiety and stress, ensuring greater safety and effectiveness of treatment.